Preparation of anatase form of TiO2 thin film at room temperature by electrochemical method as an alternative electron transport layer for inverted type organic solar cells - Keskin, Ayse V.; Gencten, Metin; Bozar, Sinem; Arvas, Melih B.; Gunes, Serap; Sahin, Yucel (ELSEVIER SCIENCE SA, 2020)
In this work, titanium dioxide thin films in rutile and anatase forms were prepared on pencil graphite and indium tin oxide electrodes, respectively by using an electrochemical method in one-step and room temperature. X-ray diffraction analyses were performed on the as prepared samples. The surface morphology of the electrodeposited TiO2 electrodes was characterized by scanning electron microscope and atomic force microscope. We have observed that the choice of the substrate affects the form of the electrodeposited thin TiO2 layers as rutile and anatase. When the pencil graphite electrode was used as a substrate rutile form of TiO2 was obtained on the electrode surface whereas anatase form of TiO2 was obtained when indium thin oxide electrode surface was used. We have also fabricated inverted type organic solar cells by employing TiO2 layer as an electron transport layer. We achieved a power conversion efficiency of 2.3%.
Keywords: Metal Oxide; Titanium dioxide; Electron transport layer, Inverted organic solar cell; Electrochemical method; TITANIUM-DIOXIDE; RUTILE; NANOPARTICLES; EFFICIENCY; SURFACE; PERFORMANCE; EVOLUTION; NANORODS; TIOSO4; Materials Science; Physics